Pemanfaatan Larutan Ekstrak Belimbing Wuluh (Averrhoa bilimbi L.) Terhadap Daya Tetas Telur Ikan Mas (Cyprinus carpio) - Febriansyah, Febriansyah; Monoarfa, Vini Desiyanti (Jurnal Biologi Babasal, 2024)
Carp (Cyprinus carpio Linnaeus, 1758) is a species of freshwater fish that has great opportunities for cultivation development to meet increasing market needs. One of the obstacles faced in goldfish cultivation is disease attacks, both at the hatchery level and at the grow-out level. Starfruit (Averrhoa bilimbi L.) is a fruit plant native to Indonesia that contains flavonoid compounds which have antibacterial, antiviral and antifungal properties, so it has the potential to be used to control disease in aquaculture organisms. This research aims to determine the benefits of starfruit extract solution on the hatchability of goldfish eggs. Administration of 1.2 mL/L starfruit extract solution. The results of the study showed that the use of starfruit extract could increase the hatchability of goldfish eggs, but the higher the dose of starfruit extract used, the lower the hatchability of goldfish eggs. A solution of starfruit extract with a dose of 0.4 mL/L produced the highest hatchability of 77.22%.